Production of bioethanol from Saccharum spontaneum by simultaneous saccharification and electro-fermentation using mixed culture of microbes. Issue 2 (7th February 2023) - Dhungana, Pradip; Prajapati, Bikram; Bhatt, Puja; Regmi, Dikshya; Yadav, Mukesh; Maharjan, Sujeeta; Lamsal, Usha; Kathariya, Sanoj; Chaudhary, Pradip; Joshi, Jarina
Abstract: Fungal consortium of a cellulolytic isolate F1 ( Aspergillus niger ) and/or ligninocellulolytic isolate F2 ( Ganoderma sessile ) along with Saccharomyces cerevisiae (CDBT2) were used for integrated approach of saccharification, fermentation and electrofermentation of Saccharum spontaneum biomass to produce ethanol. Different consortium sets of these isolates were used to observe fermentation efficiency. All the analysis were done using crude as well as hot water pretreated S. spontaneum powder to compare the ethanol production efficiency. The ethanol yield was found to be higher in crude biomass compared to hot water pretreated S. spontaneum biomass. At 28°C, 80 rpm and 5.0 pH, simultaneous culture with combination of G. sessile and CDBT2 produced higher amount of ethanol (57 mg/g crude biomass) followed by combination of G. sessile, A. niger and CDBT2 (44 ± 0.18 mg/g crude biomass). However, the amount of phenol and furfural generated were very low in both cases. In addition, electro-fermentation enhanced ethanol production by 12% and 18% with a combination culture of G. sessile, CDBT2 and G. sessile, A. niger, CDBT2 respectively. This method of lignocellulosic ethanol production by simultaneous saccharification and electrofermentation can be developed as an alternative approach for cost effective production of bioethanol.